Multiparous Ewe as a Model for Teaching Vaginal Hysterectomy Techniques. Issue 6 (December 2017) - Kerbage, Yohan; Cosson, Michel; Hubert, Thomas; Giraudet, Géraldine
Abstract : BACKGROUND: Despite being linked to improving patient outcomes and limiting costs, the use of vaginal hysterectomy is on the wane. Although a combination of reasons might explain this trend, one cause is a lack of practical training. An appropriate teaching model must therefore be devised. Currently, only low-fidelity simulators exist. Ewes provide an appropriate model for pelvic anatomy and are well-suited for testing vaginal mesh properties. This article sets out a vaginal hysterectomy procedure for use as an education and training model. METHOD: A multiparous ewe was the model. Surgery was performed under general anesthesia. The ewe was in a lithotomy position resembling that assumed by women on the operating table. EXPERIENCE: Two vaginal hysterectomies were performed on two ewes, following every step precisely as if the model were human. Each surgical step of vaginal hysterectomy performed on the ewe and on a woman were compared side by side. We identified that all surgical steps were particularly similar. The main limitations of this model are costs ($500/procedure), logistic problems (housing large animals), and public opposition to animal training models. CONCLUSION: The ewe appears to be an appropriate model for teaching and training of vaginal hysterectomy. Abstract : The multiparous ewe appears to be an excellent model for teaching vaginal hysterectomy techniques.